Pengaruh Kepercayaan dan Risiko terhadap Minat Belanja Online Shopee pada Mahasiswa Universitas Tulang Bawang Lampung - Sartika, Ella; Suhartina; Suradi (Business Perspective Journal, 2025)
Shopee officially entered Indonesia in 2015 and Shopee has become one of the most popular sites frequently visited. With Shopee, it makes it easier to shop online via gadgets anywhere and anytime as long as you have an internet connection. This research aims to determine the influence of trust and risk on Shopee online shopping interest among students at Tulang Bawang University, Lampung. The population of this research is students from Tulang Bawang University, Lampung with a sample of 100 respondents. The type of this research is quantitative with a causal associative approach using data collection techniques in the form of questionnaires. The data analysis methods used are multicollinearity test, autocorrelation test, multiple linear regression analysis, t test and F test. The results of this study show that Trust has a positive and significant effect on Shopee online shopping interest among Tulang Bawang University Students in Lampung with a greater t value. from ttable 11.053>1.988 with a significance value of 0.0011.988 with a significance value of 0.0013.09 Ftable with a significance level of 0.001 Keywords: trust, shopee online shopping interest, risk